Effect of Watch-Type Haptic Metronome on the Quality of Cardiopulmonary Resuscitation: A Simulation Study - Choi, Boram; Kim, Taerim; Yoon, Sun Young; Yoo, Jun Sang; Won, Ho-Jeong; Kim, Kyunga; Kang, Eun Jin; Yoon, Hee; Hwang, Sung Yeon; Shin, Tae Gun; Sim, Min Seob; Cha, Won Chul (Healthcare informatics research, 2019)
The aim of this study was to test the applicability of haptic feedback using a smartwatch to the delivery of cardiac compression (CC) by professional healthcare providers. A prospective, randomized, controlled, case-crossover, standardized simulation study of 20 medical professionals was conducted. The participants were randomly assigned into haptic-first and non-haptic-first groups. The primary outcome was an adequate rate of 100-120/min of CC. The secondary outcome was a comparison of CC rate and adequate duration between the good and bad performance groups. The mean interval between CCs and the number of haptic and non-haptic feedback-assisted CCs with an adequate duration were insignificant. In the subgroup analysis, both the good and bad performance groups showed a significant difference in the mean CC interval between the haptic and non-haptic feedback-assisted CC groups-good: haptic feedback-assisted (0.57-0.06) vs. non-haptic feedback-assisted (0.54-0.03), < 0.001; bad: haptic feedback-assisted (0.57-0.07) vs. non-haptic feedback-assisted (0.58-0.18), = 0.005-and the adequate chest compression number showed significant differences- good: haptic feedback-assisted (1,597/75.1%) vs. non-haptic feedback-assisted (1,951/92.2%), < 0.001; bad: haptic feedbackassisted (1,341/63.5%) vs. non-haptic feedback-assisted (523/25.4%), < 0.001. A smartwatch cardiopulmonary resuscitation feedback system could not improve rescuers' CC rate. According to our subgroup analysis, participants might be aided by the device to increase the percentage of adequate compressions after one minute.